Critical and heterotopic urbanism. Agglomeration, de-agglomeration and crisis of the contemporary city - Ojeda, Rafael (2018)
This research has as a subject of analysis, from the approach and problematization of disruptive events, the crisis of the contemporary city, urban crisis product of anomalous processes present in the geography of the city, once a primordial reference of the good and civilized life, but that over the years has gone on to experience a number of negatively synergistic processes, simultaneous processes of urban agglomeration and social deagglomeration, addressed from a historical-urban review that assesses, above all the transformations experienced in the city during the last fifty years years, period in which urban complexes have begun to be affected by constant transformations, experiencing a contradictory and emerging trend towards reengineering and urban obsolescence, with the resignification of their geographical and social spaces, which is producing critical and heterotopic reactions, via a proc that of overextension in which suburbia is being cannibalised by the constant growth of the great metropolises, transforming itself into expansive, overflowing and chaotic megalopolises, but which face that protean image of collapsed, gentrified and modern cities via technology.